The Influence of Corporate Social Responsibility, Ownership Structure, and Enterprise Risk Management on the Company's Financial Performance - Nadiva Zahrani Wibowo; Indri Kartika (Journal of Organizational Performance and Analysis, 2026)
The analysis examines the influence of Corporate Social Responsibility (CSR), foreign ownership, managerial ownership, institutional ownership, Enterprise Risk Management (ERM) on firm financial performance. Return on Assets (ROA) is a metric employed to appraise financial performance. Oil and gas businesses registered on the Indonesia Stock Exchange (IDX) between 2022 and 2024 make up population. 32 businesses were chosen as samples utilizing purposive sampling. Multiple linear regression was employed to appraise the data. These findings reveal that CSR, managerial ownership, institutional ownership have positive but insignificant effects to financial performance. This financial performance of the company is positively and significantly impacted by ERM, while foreign ownership also has a negligible impact. These results indicate that effective risk management execution acts an vital part in improving operational stability also efficiency. The research is intended to provide insights for company management and investors in evaluating factors that influence financial performance, particularly in oil and gas sector companies.